2008
DOI: 10.1111/j.1365-2982.2008.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of oesophageal wall in patients with nutcracker oesophagus and ineffective oesophageal motility

Abstract: The pathogenesis of nutcracker oesophagus (NE) and ineffective oesophageal motility (IEM) is unclear. Damage to the enteric nervous system or smooth muscle can cause oesophageal dysmotility. We tested the hypothesis that NE and IEM are associated with abnormal muscular or neural constituents of the oesophageal wall. Oesophageal manometry was performed in patients prior to total gastrectomy for gastric cancer. The oesophageal manometries were categorized as normal (n = 7), NE (n = 13), or IEM (n = 5). Histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
1
33
0
2
Order By: Relevance
“…The latter two areas were not studied here because our focus was on the possible location of neurons within the muscle strips that were examined physiologically. Our findings in the LEC region also match those by Kim et al (2008), who observed Pgp9.5 neuronal structures buried within muscular layers of esophageal wall of patients with esophageal myopathies. Because our and Kim's studies are the first to examine the location of neuronal structures in the GEJ of humans using specific neuronal markers, perhaps the location of these neurons are in fact not atypical but the norm.…”
Section: Discussionsupporting
confidence: 80%
“…The latter two areas were not studied here because our focus was on the possible location of neurons within the muscle strips that were examined physiologically. Our findings in the LEC region also match those by Kim et al (2008), who observed Pgp9.5 neuronal structures buried within muscular layers of esophageal wall of patients with esophageal myopathies. Because our and Kim's studies are the first to examine the location of neuronal structures in the GEJ of humans using specific neuronal markers, perhaps the location of these neurons are in fact not atypical but the norm.…”
Section: Discussionsupporting
confidence: 80%
“…(28) Alternatively, as all five of these patients demonstrated RRCs, the potential remains that hypercontractility (and retrograde contractions as a response to distension) are related to an imbalance of inhibitory and excitatory neural regulation. (29, 30) Future studies evaluating a greater number of asymptomatic controls and patients with HRM-defined spastic motor disorders, as well as patients with mechanical esophageal obstruction, will clarify the clinical significance of RRCs and aid refinement of the FLIP topography motility classification.…”
Section: Discussionmentioning
confidence: 99%
“…That the pathogenesis of PMED and achalasia may be related, is supported by transition of nutcracker esophagus(21, 22) and diffuse spasm(23, 24) to achalasia and by myenteric lymphocytic inflammation in the distal esophagus of 23% (3/13) of patients with nutcracker esophagus. (25)…”
Section: Discussionmentioning
confidence: 99%